The THE INFLUENCE OF PRODUCT QUALITY AND STORE ATMOSPHERE ON PURCHASE DECISIONS (CASE STUDY OF KOPI KENANGAN IN SUBANG) - sania reswa, nanda; Bismantara, Bismantara (JABI (Journal of Accounting and Business Issues), 2026)
This study aims to analyze the influence of product quality and store atmosphere on purchase decisions. The data analyzed were obtained from questionnaires filled out by 100 respondents who had previously purchased products from Kopi Kenangan in Subang. This research uses a descriptive verificative method with a quantitative approach. The data consist of primary data collected through questionnaires and secondary data obtained from literature studies. The sampling technique used is non-probability sampling with a purposive sampling method. The data analysis technique applied in this study is multiple linear regression analysis, supported by classical assumption tests and hypothesis testing using IBM SPSS Statistics 25. The results of this study indicate that simultaneously, product quality and store atmosphere have a significant effect on purchasing decisions, with a significance value of 0.000 < 0.05. Partially, product quality has a positive and significant effect on purchasing decisions with a t-value of 4.425 > t-table 1.985 and a significance value of 0.000 < 0.05. In addition, store atmosphere also has a positive and significant effect on purchasing decisions with a t-value of 2.914 > t-table 1.985 and a significance value of 0.004 < 0.05. The coefficient of determination (R Square) is 0.540, indicating that product quality and store atmosphere explain 54% of purchasing decisions, while the remaining 46% is influenced by other variables not examined in this study.